Sequential Therapy of Nadroparin and Rivaroxaban in the Initial Treatment of Patients With Acute Pulmonary Embolism - Xiong, Wei; Zhao, Yunfeng; Liu, Song; Du, He; Wang, Yanmin; Li, Wenjie; Guo, Xuejun (Frontiers in Pharmacology, 2022)
Background: Sequential low molecular weight heparin (LMWH) plus warfarin, LMWH plus edoxaban, and LMWH plus dabigatran regimens have already shown efficacy and safety in the treatment of acute pulmonary embolism (PE). The efficacy and safety of sequential LMWH plus rivaroxaban regimen in the treatment of acute PE have been understudied. Methods: A retrospective study was performed to explore the efficacy and safety of sequential therapy regimens of subcutaneous LMWH (nadroparin 86 IU/kg every 12 h for a week) followed by oral rivaroxaban (20 mg once daily for 3 months) for the management of patients with established acute PE without hemodynamic instability, compared with those of nadroparin plus dabigatran and nadroparin plus warfarin. Results: The number of patients with total resolution of PE were 238 (80.1%), 220 (78.0%), and 166 (62.6%), in the nadroparin + rivaroxaban, nadroparin + dabigatra, and nadroparin + warfarin groups, respectively. (p = 0.001) The prevalence of DVT at the 3-month follow-up visit was 18 (6.1%), 14 (5.0%), and 11 (4.2%), in the aforementioned three groups, respectively. (p = 0.559) The NT-proBNP level (pg/ml) at the 3-month follow-up visit was 122.5 (97.4–158.9), 131.7 (102.2–166.3), and 357.8 (275.4–433.2) in the three groups, respectively. (p = 0.001) The D-dimer level (ng/ml) at the 3-month follow-up visit was 387.3 (310.9–465.2), 432.5 (382.4–489.6), and 854.0 (721.5–993.7) in the three groups, respectively (p < 0.001). The number of patients with major bleeding events was 3(0.9%), 6(1.8%), and 18 (5.5%) in the three groups, respectively (p < 0.001). Conclusion: The regimen of sequential subcutaneous nadroparin at body-weight adjusted dose for a week followed by oral rivaroxaban at a dose of 20 mg once daily for 3 months is effective and safe in the initial treatment of patients with acute pulmonary embolism.